2021
DOI: 10.3389/fnut.2021.765543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early vs. Late Time-Restricted Eating on Cardiometabolic Health, Inflammation, and Sleep in Overweight and Obese Women: A Study Protocol for the ChronoFast Trial

Abstract: Background: Time-restricted eating is a promising dietary strategy for weight loss, glucose and lipid metabolism improvements, and overall well-being. However, human studies demonstrated contradictory results for the restriction of food intake to the beginning (early TRE, eTRE) or to the end of the day (late TRE, lTRE) suggesting that more carefully controlled studies are needed.Objective: The aim of the ChronoFast trial study is to determine whether eTRE or lTRE is a better dietary approach to improve cardiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 89 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…Another area of interest is assessing how the timing of the eating window may affect glucose outcomes as there is both pre‐clinical and clinical evidence that the 24‐h circadian rhythm, which is synchronized with behavioral and environmental patterns, impacts nutrient utilization and storage 32 . Upcoming trials will further examine changes in continuous glucose and glycemic parameters in early versus late TRE interventions 66 . It is of particular importance to determine whether late TRE results in cardiometabolic improvements, given that many individuals attempting to follow TRE prefer a delayed eating window to better align with social eating occasions 67 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another area of interest is assessing how the timing of the eating window may affect glucose outcomes as there is both pre‐clinical and clinical evidence that the 24‐h circadian rhythm, which is synchronized with behavioral and environmental patterns, impacts nutrient utilization and storage 32 . Upcoming trials will further examine changes in continuous glucose and glycemic parameters in early versus late TRE interventions 66 . It is of particular importance to determine whether late TRE results in cardiometabolic improvements, given that many individuals attempting to follow TRE prefer a delayed eating window to better align with social eating occasions 67 .…”
Section: Discussionmentioning
confidence: 99%
“…There are fortunately several upcoming studies that will further assess the role of TRE in glucose metabolism with the use of CGM 64–66 . This is particularly important in populations with dysglycemia at baseline as most studies to date that have found favorable changes in continuous glucose profiles or glycemic parameters have been in individuals with baseline‐impaired glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advocates of time-restricted eating have mainly focused on early time-restricted eating, resulting in a long interval between the last meal of the day and bedtime [ 54 ]. In a study of 90 healthy subjects, early time-restricted eating (6:00–15:00) was more effective than midday time-restricted eating (11:00–20:00) in improving insulin sensitivity.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…In contrast, TRF is a dietary approach defined as feeding within a period of ≤10 h and fasting for at least 14 h a day, where feeding is consolidated to the active period, aligning peripheral and central circadian rhythms [ 121 ]. This strategy could be divided into early (8 a.m. to 4 p.m.) and late (1 p.m. to 9 p.m.) [ 122 ]. When applied to human populations, TRF does not restrict the number of calories consumed or require a dietary profile of macronutrients, making it easier for patients to adopt.…”
Section: Chrononutrition In the Management Of Nafldmentioning
confidence: 99%